Predominant enteropathogens in acute diarrhea and associated variables in children at the Lambayeque Regional Hospital, Peru - Ipanaque-Chozo, Jhonatan (2017)
Objective: To determine the type and frequency of predominant enteropathogens in acute diarrhea and their associated characteristics in children treated at Hospital Regional Lambayeque (HRL) - Peru. Materials and methods: A cross-sectional analytical study was carried out in 70 fecal samples between March and May 2015. These samples were studied by coproculture and immunochromatography for the detection of enteropathogenic bacteria and viruses, respectively, while enteroparasites were sought by direct microscopic examination, Kinyoun staining method and ELISA for the detection of coproantigens (Entamoeba histolytica, Giardia lamblia and Cryptosporidium spp). Leukocyte count and chemical tests (Benedict, Thevenon and Sudan III) were also performed for the functional study of the diarrheal disease. Results: In 48.6% of the samples, the infectious etiology of diarrhea was detected, prevailing the parasitic cause (25.8%), followed by the bacterial (17.1%) and viral (5.8%) ones. The most common enteropathogens were G. lamblia (18.6%) and Salmonella enteritidis (10.0%). An association between greater than 100 fecal leukocytes per field and the bacterial etiology (p=0.027) was observed, while less than 10 fecal leukocytes per field (p=0.002) and a positive Sudam III test (p=0.003) were associated with the parasitic etiology. Conclusions: In more than half of the samples (51.4%) the infectious etiology of diarrhea could not be proven, whereas Giardia lamblia was the most frequent cause of diarrhea in the studied population. However, it is necessary to implement more sensitive and specific techniques for the detection of a greater range of enteropathogens with which to improve the diagnosis and treatment of the disease.